Investigation of Psychophysiological and Subjective Effects of Long Working Hours – Do Age and Hearing Impairment Matter? - Wagner-Hartl, Verena; Kallus, K. Wolfgang (Frontiers in Psychology, 2018)
Following current prognosis, demographic development raises expectations of an aging of the working population. Therefore, keeping employees healthy and strengthening their ability to work, becomes more and more important. When employees become older, dealing with age-related impairments of sensory functions, such as hearing impairment, is a central issue. Recent evidence suggests that negative effects that are associated with reduced hearing can have a strong impact at work. Especially under exhausting working situations such as working overtime hours, age and hearing impairment might influence employees’ well-being. Until now, neither the problem of aged workers and long working hours, nor the problem of hearing impairment and prolonged working time has been addressed explicitly. Therefore, a laboratory study was examined to answer the research question: Do age and hearing impairment have an impact on psychophysiological and subjective effects of long working hours. In total, 51 white-collar workers, aged between 24 and 63 years, participated in the laboratory study. The results show no significant effects for age and hearing impairment on the intensity of subjective consequences (perceived recovery and fatigue, subjective emotional well-being and physical symptoms) of long working hours. However, the psychophysiological response (the saliva cortisol level) to long working hours differs significantly between hearing impaired and normal hearing employees. Interestingly, the results suggest that from a psychophysiological point of view long working hours were more demanding for normal hearing employees.